Zipping Minds - Papadima, Aspasia (My University, 2026)
Participation as an invited graphic artist in the 3rd Emirates International Poster Festival themed "Connecting Minds, Creating the Future", with an original graphic artwork titled "Zipping Minds". 8-13 November 2021. Organized by the Cultural and Scientific Association (NADWA) in Dubai. The artwork is also published in page 33 of the exhibition catalogue for the event.